The Role of Zinc in Acute Bronchiolitis in children less than 2 years old - Hyder, Rumy Tabrez; Ahmed, Shafi; Yasmeen, B H Nazma (Northern International Medical College Journal, 2023)
Background: Bronchiolitis is an acute respiratory illness which is the leading cause of respiratory distress in infancy and early childhood with its greatest morbidity in infants. Although zinc supplementation is effective in both preventing and treating pneumonia but its role in acute bronchiolitis has rarely been examined. Objective: To assess the effect of zinc sulfate to improve the clinical manifestations of acute bronchiolitis (Severe cases) in children less than 2 years of age. Materials and Methods: This was a double blind randomized clinical trial on 70 patients aged 2 to 23 months admitted in the Pediatric ward of Khwaja Yunus Ali Medical College and Hospital from September 2019 to September 2020 with the diagnosis of acute bronchiolitis. Patients were randomly divided equally into 2 groups: a case group was assigned oral zinc sulfate and the control group received placebo. Results: Mean age of case group was 174.63±98.7 days and control group 176.86±97.43 days ( p=0.924) with male predominance in both groups. Symptoms and signs of acute bronchiolitis (Severe cases) were compared between the 2 groups during admission and then at 24, 48 and 72 hours after initiation of treatment. No statistically significant differences were observed between the 2 groups in improvement of symptoms and signs including fever, fast breathing, chest indrawing and wheezing on 48 and 72 hours after treatment with zinc sulfate ( p>0.05). The duration of hospitalization was 4.2±2.6 days in the case group and 4.4±2.2 days in the control group and this difference was not significant. Conclusion: The present study showed that zinc sulfate has no benefit in improving the clinical manifestations of acute bronchiolitis. Northern International Medical College Journal Vol. 12 No.2 Jan 2021, Page 535-538